Fine Structure of Protoplasts and L-Forms of Clostridium botulinum Types A and E - Brown, George W. (1971)
Spherical bodies, that are obtained by adding penicillin and lysozyme to Clostridium botulinum types E and A cultures which are growing in an osmotically stabilized medium, are shown to be protoplasts by electron microscopy. The L-forms of these two culture types have morphologically different inclusion bodies.